Considering BCG vaccination to reduce the impact of COVID-19 - Curtis, Nigel; Sparrow, Annie; Ghebreyesus, Tedros A; Netea, Mihai G (The Lancet (British edition), 2020)
In addition to its specific effect against tuberculosis, the BCG vaccine has beneficial nonspecific (off-target) effects on the immune system that protect against a wide range of other infections and are used routinely to treat bladder cancer.1,2 This has led to the suggestion that vaccination with BCG might have a role in protecting health-care workers and other vulnerable individuals against severe coronavirus disease 2019 (COVID-19). In Guinea-Bissau, a high-mortality setting, BCG-Danish reduced all-cause neonatal mortality by 38% (95% CI 17–54), mainly because there were fewer deaths from pneumonia and sepsis.3 In South Africa, BCG-Danish reduced respiratory tract infections by 73% (95% CI 39–88) in adolescents.4 Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a single-stranded positive-sense RNA virus, and the BCG vaccine has been shown to reduce the severity of infections by other viruses with that structure in controlled trials. [...]whether BCG will be effective remains unknown: findings from the ecological studies suggesting less COVID-19 in countries with routine BCG immunisation are weak evidence because they are based on population rather than individual data and are prone to confounding.11 Also, it is unlikely that a BCG vaccine given decades ago in childhood will ameliorate COVID-19 now.